Parental health and children’s cognitive and non-cognitive development: New evidence from the Longitudinal Survey of Australian Children - Nguyen, Ha Trong; Le, Huong Thu (My University, 2017)
This paper examines the effects of parental health on cognitive and noncognitive development in Australian children. The underlying nationally representative panel data and a child fixed effects estimator are used to deal with unobserved heterogeneity. We find that only father's serious mental illness worsens selected cognitive and noncognitive skills of children. Maternal poor health also deteriorates some cognitive and noncognitive outcomes of children of lone mothers only. Our results demonstrate that either failing to account for parent–child fixed effects or using child noncognitive skills reported by parents could overestimate the harmful impact of poor parental health on child development.
Keywords: Health; Intergenerational Transfer; Intergenerational transfer; Health and wellbeing; Health; Intergenerational Transfer; Intergenerational transfer; Health and wellbeing